Who Benefits from Multispecies Justice? Review of The Promise of Multispecies Justice, ed. Sophie Chao, Karin Bolender, and Eben Kirksey (2022) - Otjen, Nathaniel (Humanimalia, 2024)
Review of: Sophie Chao, Karin Bolender, and Eben Kirksey, eds. The Promise of Multispecies Justice. Durham, NC: Duke University Press, 2022. xii + 284 pp. 23 illus. 99.95 (hb) 978-1-4780-1625-0, 26.95 (pb) 978-1-4780-1889-6